BIO-SYNGAS DERIVED FROM INDONESIAN OIL PALM EMPTY FRUIT BUNCH (EFB) USING MIDDLE-SCALE GASIFICATION - Pradana, Yano Surya; Budiman, Arief (Taylor's University College, 2015)
Indonesia now is the largest producer of palm oil in the world. Over seven million hectares in the cultivation and more than 400 palm oil mills in operation. The major biomass by product from the palm oil industry is empty fruit bunches (EFB) that have a great potency as basic feedstock used for alternative energy. We proposed new technology that combined pyrolysis-catalytic cracking-gasification processes in a whole system, namely as integrated autothermal technology. By using this technology, energy supplied to the system can be reduced significantly. In this study, Indonesian oil palm empty fruit bunches (EFB) was converted to alternative energy using a middle-scale gasification. The products were bio-syngas, bio-oil, water-phase and char. The effects of various gasification temperatures and air volumetric flow rates on the yields of the products were investigated. The temperature of gasification and air volumetric flow rate were varied in the range of 500-700 °C and 29-55 ml/second, respectively. Product yields were found to be significantly influenced by the gasification conditions. Under the experimental conditions, the maximum bio-syngas yield was 45.50 %wt obtained at 700 °C, with air volumetric flow rate of 41 ml/second.